Design and fabrication of a new circularly polarised 2 × 3 antenna array for rectenna system. (2017) - Sennouni, Mohamed Adel; Zbitou, Jamal; Abboud, Benaissa; Tribak, Abdelwahed; Bennis, Hamid; Latrach, Mohamed
Microwave power transmission (MPT) is an alternative energy solution to supply power to the electrical and electronics equipment without a wired connection. This paper presents an antenna array design which is the crucial part in a rectenna (rectifier + antenna) system. The developed design consists of a new 2 × 3 antenna array having an operating frequency at 2.45 GHz ISM band with inclined slots at the centre of each antenna element to improve the circular polarisation and V-shaped slots to enhance the bandwidth around the operating frequency. The proposed design has an overall size of 26.18 × 11.86 cm², and provides a high directivity of 9.14 dBi. Also, it occurs an enhanced radiation efficiency of about 98%. Simulation and measurement results are in good agreement which make this antenna very suitable for MPT applications.